Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Proteomic analysis of human plasma in chronic rheumatic mitral stenosis reveals proteins involved in the complement and coagulation cascade - Mukherjee, Somaditya; Jagadeeshaprasad, Mashanipalya G.; Banerjee, Tanima; Ghosh, Sudip K.; Biswas, Monodeep; Dutta, Santanu; Kulkarni, Mahesh J.; Pattari, Sanjib; Bandyopadhyay, Arun (Clinical Proteomics, 2014)
Background: Rheumatic fever in childhood is the most common cause of Mitral Stenosis in developing countries. The disease is characterized by damaged and deformed mitral valves predisposing them to scarring and narrowing (stenosis) that results in left atrial hypertrophy followed by heart failure. Presently, echocardiography is the main imaging technique used to diagnose Mitral Stenosis. Despite the high prevalence and increased morbidity, no biochemical indicators are available for prediction, diagnosis and management of the disease. Adopting a proteomic approach to study Rheumatic Mitral Stenosis may therefore throw some light in this direction. In our study, we undertook plasma proteomics of human subjects suffering from Rheumatic Mitral Stenosis (n = 6) and Control subjects (n = 6). Six plasma samples, three each from the control and patient groups were pooled and subjected to low abundance protein enrichment. Pooled plasma samples (crude and equalized) were then subjected to in-solution trypsin digestion separately. Digests were analyzed using nano LC-MSE. Data was acquired with the Protein Lynx Global Server v2.5.2 software and searches made against reviewed Homo sapiens database (UniProtKB) for protein identification. Label-free protein quantification was performed in crude plasma only.

Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Rifampicin reduces advanced glycation end products and activates DAF-16 to increase lifespan in Caenorhabditis elegans - Golegaonkar, Sandeep; Tabrez, Syed S.; Pandit, Awadhesh; Sethurathinam, Shalini; Jagadeeshaprasad, Mashanipalya G.; Bansode, Sneha B.; Sampathkumar, Srinivasa-Gopalan; Kulkarni, Mahesh J.; Mukhopadhyay, Arnab (Aging Cell, 2015)
Advanced glycation end products (AGEs) are formed when glucose reacts nonenzymatically with proteins; these modifications are implicated in aging and pathogenesis of many age-related diseases including type II diabetes, atherosclerosis, and neurodegenerative disorders. Thus, pharmaceutical interventions that can reduce AGEs may delay age-onset diseases and extend lifespan. Using LC-MSE, we show that rifampicin (RIF) reduces glycation of important cellular proteins in vivo and consequently increases lifespan in Caenorhabditis elegans by up to 60%. RIF analog rifamycin SV (RSV) possesses similar properties, while rifaximin (RMN) lacks antiglycation activity and therefore fails to affect lifespan positively. The efficacy of RIF and RSV as potent antiglycating agents may be attributed to the presence of a p-dihydroxyl moiety that can potentially undergo spontaneous oxidation to yield highly reactive p-quinone structures, a feature absent in RMN. We also show that supplementing rifampicin late in adulthood is sufficient to increase lifespan. For its effect on longevity, rifampicin requires DAF-18 (nematode PTEN) as well as JNK-1 and activates DAF-16, the FOXO homolog. Interestingly, the drug treatment modulates transcription of a different subset of DAF-16 target genes, those not controlled by the conserved Insulin-IGF-1-like signaling pathway. RIF failed to increase the lifespan of daf-16 null mutant despite reducing glycation, showing thereby that DAF-16 may not directly affect AGE formation. Together, our data suggest that the dual ability to reduce glycation in vivo and activate prolongevity processes through DAF-16 makes RIF and RSV effective lifespan-extending interventions.
Keywords: advanced glycation end products; aging; Caenorhabditis elegans; DAF-16; Glycation; lifespan; rifampicin

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.

Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry

Abundance matters: role of albumin in diabetes, a proteomics perspective - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Kulkarni, Mahesh J. (Expert Review of Proteomics, 2017)
Introduction: Human serum albumin (HSA) is a multifaceted protein with vital physiological functions. It is the most abundant plasma protein with inherent capability to bind to diverse ligands, and thus susceptible to various post-translational modifications (PTMs) which alter its structure and functions. One such PTM is glycation, a non-enzymatic reaction between reducing sugar and protein leading to formation of heterogeneous advanced glycation end products (AGEs). Glycated albumin (GA) concentration increases significantly in diabetes and is implicated in development of secondary complications. Areas covered: In this review, we discuss in depth formation of GA and its consequences, approaches used for characterization and quantification of GA, milestones in GA proteomics, clinical relevance of GA as a biomarker, significance of maintaining abundant levels of albumin and future perspectives. Expert commentary: Elevated GA levels are associated with development of insulin resistance as well as secondary complications, in healthy and diabetic individuals respectively. Mass spectrometry (MS) based approaches aid in precise characterization and quantification of GA including early and advanced glycated peptides, which can be useful in prediction of the disease status. Thus GA has evolved to be one of the best candidates in the pursuit of diagnostic markers for prediction of prediabetes and diabetic complications.

Glycation inhibitors extend yeast chronological lifespan by reducing advanced glycation end products and by back regulation of proteins involved in mitochondrial respiration - Kazi, Rubina S.; Banarjee, Reema M.; Deshmukh, Arati B.; Patil, Gouri V.; Jagadeeshaprasad, Mashanipalya G.; Kulkarni, Mahesh J. (Journal of Proteomics, 2017)
Advanced Glycation End products (AGEs) are implicated in aging process. Thus, reducing AGEs by using glycation inhibitors may help in attenuating the aging process. In this study using Saccharomyces cerevisiae yeast system, we show that Aminoguanidine (AMG), a well-known glycation inhibitor, decreases the AGE modification of proteins in non-calorie restriction (NR) (2% glucose) and extends chronological lifespan (CLS) similar to that of calorie restriction (CR) condition (0.5% glucose). Proteomic analysis revealed that AMG back regulates the expression of differentially expressed proteins especially those involved in mitochondrial respiration in NR condition, suggesting that it switches metabolism from fermentation to respiration, mimicking CR. AMG induced back regulation of differentially expressed proteins could be possibly due to its chemical effect or indirectly by glycation inhibition. To delineate this, Metformin (MET), a structural analog of AMG and a mild glycation inhibitor and Hydralazine (HYD), another potent glycation inhibitor but not structural analog of AMG were used. HYD was more effective than MET in mimicking AMG suggesting that glycation inhibition was responsible for restoration of differentially expressed proteins. Thus glycation inhibitors particularly AMG, HYD and MET extend yeast CLS by reducing AGEs, modulating the expression of proteins involved in mitochondrial respiration and possibly by scavenging glucose. Significance: This study reports the role of glycation in aging process. In the non-caloric restriction condition, carbohydrates such as glucose promote protein glycation and reduce CLS. While, the inhibitors of glycation such as AMC, HYD, MET mimic the caloric restriction condition by back regulating deregulated proteins involved in mitochondria( respiration which could facilitate shift of metabolism from fermentation to respiration and extend yeast CLS. These findings suggest that glycation inhibitors can be potential molecules that can be used in management of aging. (C) 2017 Elsevier B.V. All rights reserved.

Multipronged quantitative proteomics reveals serum proteome alterations in breast cancer intrinsic subtypes - Gajbhiye, Akshada; Dabhi, Raju; Taunk, Khushman; Jagadeeshaprasad, Mashanipalya G.; RoyChoudhury, Sourav; Mane, Anupama; Bayatigeri, Santhakumari; Chaudhury, Koel; Santra, Manas K.; Rapole, Srikanth (Journal of Proteomics, 2017)
Being molecularly heterogeneous, breast cancer tends to be a complicated oncological disease with high incidence rates throughout the world. The primary aim of this study was to identify the set of serum proteins with discriminatory capabilities towards the four major subtypes of breast cancer. We employed multipronged quantitative proteomic approaches like 2D-DIGE, iTRAQ and SWATH-MS and identified 307 differentially regulated proteins. Luminal A subtype consisted of 24, Luminal B subtype 38, HER2 Enriched subtype 17 and Triple negative breast cancer subtype 10 differentially regulated subtype specific proteins. These specific proteins were further subjected to bioinformatic tools which revealed the involvement in platelet degranulation, fibrinolysis, lipid metabolism, immune response, complement activation, blood coagulation, glycolysis and cancer signaling pathways in the subtypes of the breast cancer. The significant discrimination efficiency of the models generated through multivariate statistical analysis was decent to distinguish each of the four subtypes from controls. Further, some of the statistically significant differentially regulated proteins were verified and validated by immunoblotting and mass spectrometry based selected reaction monitoring (SRM) approach. Our Multipronged proteomics approaches revealed panel of serum proteins specifically altered for individual subtypes of breast cancer. The mass spectrometry data are available via ProteomeXchange with identifier PXD006441. Biological significance: Worldwide, breast cancer continues to be one of the leading causes of cancer related deaths in women and it encompasses four major molecular subtypes. As breast cancer treatment majorly depends on identification of specific subtype, it is important to diagnosis the disease at subtype level. Our results using multipronged quantitative proteomics identified 307 differentially regulated proteins in which 24 were specific for Luminal A, 38 for Luminal B, 17 for HER2 enriched and 10 proteins were specific for TN subtype. Bioinformatic analysis of these proteins revealed certain biological processes and pathways altered at subtype level and validation experiments of some of these proteins using immunoblotting and SRM assays are consistent with discovery data. This is the first comprehensive proteomic study on serum proteome alterations at subtype level which will not only help to distinguish subtype of breast cancer but also contribute to a better understanding of the molecular characteristic of breast cancer at individual subtype level. (C) 2017 Elsevier B.V. All rights reserved.

Targeted quantification of the glycated peptides of human serum albumin - Garikapati, Vannuruswamy; Korwar, Arvind M.; Jagadeeshaprasad, Mashanipalya G.; Kulkarni, Mahesh J. (Methods in Molecular Biology, 2017)
Glycated human serum albumin (HSA) serves as an important marker for monitoring the glycemic status. Developing methods for unambiguous identification and quantification of glycated peptides of HSA using high-throughput technologies such as mass spectrometry has a great clinical significance. The following protocol describes the construction of reference spectral libraries for Amadori-modified lysine (AML), N(ε)-(carboxymethyl) lysine (CML)-, and N(ε)-(carboxyethyl)lysine (CEL)-modified peptides of synthetically modified HSA using high-resolution mass spectrometers. The protocol also describes work flows, for unambiguous identification and quantification of glycated modified peptides of HSA in clinical plasma using standard spectral libraries by various mass spectrometry approaches such as parallel reaction monitoring (PRM), sequential window acquisition of all theoretical fragment ion spectra (SWATH), and MSE.

Albumin abundance and its glycation Status determine hemoglobin glycation - Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2018)
Diabetes diagnosis and management majorly depend upon the measurement of glycated hemoglobin (HbAlc) levels. Various factors influence HbAlc levels such as the use of various analytical methods and the presence of various clinical conditions. Plasma albumin levels were known to be negatively associated with HbAlc. However, the precise mechanism by which they affect HbAlc is not well' understood. Therefore, we have studied the influence of albumin levels and its glycation status on hemoglobin glycation using erythrocyte culture experiments. Erythrocytes maintained at low albumin concentration exhibited relatively increased albumin and hemoglobin glycation as compared to that in those maintained at higher albumin concentration. Increase in albumin glycation may decrease its ability to protect hemoglobin glycation. This was demonstrated by treatment of erythrocytes with N(epsilon-(carboxymethyl)lysine-modified serum albumin (CMSA), which failed to protect hemoglobin glycation; instead, it increased hemoglobin glycation. The inability of CMSA to reduce hemoglobin glycation was due to the lack of free lysine residues of albumin, which was corroborated by using N(epsilon-(acetyI)lysine serum albumin (AcSA) and clinical diabetic plasma. This is the first study which demonstrates that the modification of lysine residues of albumin impairs its ability to inhibit hemoglobin glycation. Furthermore, correlation studies between HbAlc and albumin levels or relative albumin fructosamine from clinical subjects supported our experimental finding that albumin abundance and its glycation status influence hemoglobin glycation. Therefore, we propose albumin level and its glycation status to be quantified in conjunction with HbAlc for better management of diabetes.